Kathleen Warner Slane (with contributions by Ethne Barnes, David S. Reese and David R. Jordan). Tombs, Burials, and Commemoration in Corinth’s Northern Cemetery - Bes, Philip (Journal of Greek Archaeology, 2018)
Each of us who has experience working within longer-running archaeological projects – of which the American excavations at Corinth is a prime example – is likely at one point or another to be confronted by that particular project’s excavation, documentation and/or storage history. One wishes to (re)study, and to have a fresh look at old excavations and the associated finds, motivated for instance by new concepts, or new questions. As it may turn out, the dossier in question is incomplete (finds or records have been lost), which as such hampers the desired complete (re)interpretation.